Impact of Spirulina Supplementation on Semen Parameters in Patients with Idiopathic Male Infertility: A Pilot Randomized Trial - Modarresi, Roya; Aminsharifi, Alireza; Foroughinia, Farzaneh (Urology Journal, 2019)
Purpose: To evaluate the efficacy of therapy with spirulina supplement on semen parameters in patients with idiopathic male infertility. Materials and Methods: A total of 40 men with idiopathic infertility were randomly assigned into two groups. Group A received 2 g spirulina supplement as well as conventional regimen for the treatment of infertility selected by their physician (220 mg/day zinc sulfate, 500mg/day L-carnitine, and 50 mg/day clomiphene) during 12 weeks of the study, while group B received placebo plus conventional therapy during the study period. Semen parameters were analyzed at baseline and at the end of the study as a primary endpoint. The secondary endpoint was the rate of pregnancy occurring in the patients. wives. Result: No significant differences in semen parameters were observed between the spirulina and control groups [count (16.43 vs. 46.00, P = .164), motility (51.00 vs. 48.7, P = .008), and morphology (47.50 vs. 15.00, P = NA)]. Our results showed a pregnancy rate of 5% in the spirulina group versus 0% in the control group. Conclusion: This pilot randomized trial provides initial evidence on the possible beneficial effects of spirulina mainly in patients with impaired sperm motility or morphology. Due to the limited sample size, further larger randomized trials not only at the level of semen parameters but at the scope of paternity are required to confirm these potential benefits.